Mendorong Motivasi Wirausaha UMKM untuk Memajukan Ekonomi Masyarakat di Kelurahan Joglo Kota Jakarta Barat - Sugiharjo, R. Joko; Rahmat, Abdul; Paijan, Paijan (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2024)
Micro, Small, and Medium Enterprises (MSMEs) are business entities managed by individuals, families, or small-scale business units, classified based on annual turnover, asset volume, and workforce. Effective human resource management is essential for MSMEs in systematically organizing finances, enabling business owners to understand their financial conditions and business developments. Easy access to information on assets, liabilities, equity, cash flow, and profit fluctuations provides crucial support for MSME entrepreneurs in making strategic business decisions. This activity not only motivates entrepreneurs to maintain business continuity but also guides them towards achieving desired business and economic goals. The drive to engage in entrepreneurship stems from a strong individual desire to realize self-potential through creative and innovative thinking, creating new products that have a social and economic impact on the local community. The courage to explore and implement new ideas is reinforced by strong entrepreneurial motivation, creating a positive cycle between motivation and action that strengthens the character of resilient and high-quality entrepreneurs.